2001
DOI: 10.1046/j.1365-2133.2001.04130.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to the extracellular and intracellular domain of bullous pemphigoid 180, the putative key autoantigen in bullous pemphigoid, belong predominantly to the IgG1 and IgG4 subclasses

Abstract: Consistent with prior evidence indicating that subepidermal blister formation in BP is dependent upon complement activation, the frequent finding of complement-fixing IgG1 autoantibodies to both the ECD and ICD of BP180 might have pathogenic relevance in BP. These findings provide new insights relevant for our understanding of the immune response to BP180, the putative key autoantigen in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 54 publications
1
52
1
Order By: Relevance
“…In this study, we have directly demonstrated that anti-hCOL17 NC16A IgG1 mAb has pathogenic activity in vivo by using COL17-humanized (COL17 m2/2, h+ ) BP model mice. As previous clinical studies on BP (5,7,28), our results further support the notion that IgG1 autoantibodies against hCO17 are potent and possibly the main pathogenic IgG autoantibodies in BP.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In this study, we have directly demonstrated that anti-hCOL17 NC16A IgG1 mAb has pathogenic activity in vivo by using COL17-humanized (COL17 m2/2, h+ ) BP model mice. As previous clinical studies on BP (5,7,28), our results further support the notion that IgG1 autoantibodies against hCO17 are potent and possibly the main pathogenic IgG autoantibodies in BP.…”
Section: Discussionsupporting
confidence: 77%
“…IgG1 and IgG3 are the most effective complement activators, whereas IgG4 is not capable of fixing complements (40). Previous clinical studies demonstrated that IgG1 and IgG4 autoantibodies are major IgG subclasses of BP patient autoantibodies and that IgG2 and IgG3 are minor subclasses of BP patient autoantibodies (5,7,28). In vitro analysis using cryosections of human skin and leukocytes from healthy volunteers demonstrated that IgG1 autoantibodies purified from BP sera showed much stronger pathogenic activity than that of IgG4 autoantibodies (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the pathogenic role of autoreactive IgG4 is suspected in several autoimmune diseases, particularly dermatological bullous diseases. IgG4 towards the major autoantigens of such diseases were reported to be associated to clinical features: to disease progression and severity in Pemphigus vulgaris [53,54], to progression from a preclinical to a clinical form in P. foliaceus [55], and to a long disease duration in bullous pemphigoid [56]. Finally, IgG1 in mice (the human IgG4 counterpart) may trigger immune effector functions via FcgRIII [42], supporting our hypothesis that a particular interaction between AhFibA subclasse(s) and particular type(s) of IgG receptors may be critical in the self-maintenance of inflammation.…”
Section: Discussionmentioning
confidence: 99%